1997
DOI: 10.1017/s0022215100138782
|View full text |Cite
|
Sign up to set email alerts
|

Basal cell carcinoma of the external auditory canal and Gorlin-Goltz syndrome: a case report

Abstract: A case of nevoid basal cell carcinoma syndrome (Gorlin-Goltz syndrome) with basal cell carcinoma of the external auditory canal is reported. This is only the second such case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In the case by Lobo et al the patient presented with a BCC in the right external auditory canal, treated by a nearly circumferential excision up to the tympanic membrane. 7 Another patient with a BCC of the ear was discussed by Lasso et al The tumor originated from the temporal region and involved the middle ear, the intrapetrous part of the facial nerve and the dura mater. Resection required extensive use of local and free flaps.…”
Section: Discussionmentioning
confidence: 99%
“…In the case by Lobo et al the patient presented with a BCC in the right external auditory canal, treated by a nearly circumferential excision up to the tympanic membrane. 7 Another patient with a BCC of the ear was discussed by Lasso et al The tumor originated from the temporal region and involved the middle ear, the intrapetrous part of the facial nerve and the dura mater. Resection required extensive use of local and free flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Khalifa et al reported a case of endometrial adenocarcinoma associated with ovarian fibroma and Gorlin's syndrome. The external auditory meati may also be involved, 15,21 and orbital or tarsal BCCs may also extend into and/or obliterate the orbit and ethmoidal sinuses. 17 Yilmaz et al reported the concurrence of basal cell naevus syndrome and adenoid cystic carcinoma in a patient who also had distant metastases in the lungs, 18 a feature seen by other authors in this and other sites.…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography scans revealed a large, cystic mass in the left maxillary sinus, protruding into the nasal cavity. The external auditory meati may also be involved, 15 , 21 and orbital or tarsal BCCs may also extend into and/or obliterate the orbit and ethmoidal sinuses 8 , 22 . To date, no cases with involvement of the upper aerodigestive tract have been documented.…”
Section: Introductionmentioning
confidence: 99%